ARGUMENTATIVE POWER: A Critical Discourse Analysis to Selected Texts for Academic Purpose - Nur Najibah Sukmawati; Sukma Septian Nasution (Universitas Sulawesi Barat, 2019)
A text deserves comprehensive analyses on its textual structure as well as socio-cultural context to meet readers’ comprehension. This paper aims at (1) finding out linguistic styles of the texts and (2) identifying power struggle behind an argumentative text entitled Computer for Children: Advantages or Drawbacks? used to the third students of Informatics Engineering Department at a private university in South Tangerang, Indonesia as a material in learning argumentative text. This is a critical discourse analysis by using Fairclough’s model which consists of description, interpretation, and explanation. In analyzing the text, systemic functional linguistics is used to find out the texts’ power as well as to determine whether the texts are adoptable for the students to learn argumentative texts. The analysis concludes that (1) formal, complex, verbal, repetitive, multi-perspective, evident-based, metaphorical, and over-wording dictions underpinned in an institutionalized social activity and unspecialized semantic domain dominate the texts which conclude that (2) its power to the readers is all equal that the author provoked rather than provided, evident-based and analytical arguments of the issue.